Mucosal Invasion, but Not Incomplete Excision, Has Negative Impact on Long-Term Survival in Patients With Extramammary Paget’s Disease - Hashimoto, Hiroki; Kaku-Ito, Yumiko; Furue, Masutaka; Ito, Takamichi (Frontiers in Oncology, 2021)
Background: Extramammary Paget’s disease (EMPD) sometimes spreads from the skin to mucosal areas, and curative surgical excision of these areas is challenging. The aim of this study is to analyze the impact of mucosal involvement and surgical treatment on the survival of patients with EMPD. Methods: We conducted a retrospective review of 217 patients with EMPD. We also assessed the associations between tumor involvement in boundary areas (anal canal, external urethral meatus, vaginal introitus), prognostic factors, and survival in 198 patients treated with curative surgery. Results: Of 217 patients, 75 (34.6%) had mucosal boundary area involvement. Lesions in these areas were associated with frequent lymphovascular invasion (p = 0.042), lymph node metastasis (p = 0.0002), incomplete excision (p < 0.0001), and locoregional recurrence (p < 0.0001). Boundary area involvement was an independent prognostic factor associated with disease-specific survival, per multivariate analysis (HR: 11.87, p = 0.027). Incomplete excision was not significantly correlated with disease-specific survival (HR: 1.05, p = 0.96). Conclusion: Boundary area tumor involvement was a major risk factor for incomplete excision, local recurrence, and poor survival outcomes. However, incomplete removal of primary tumors was not significantly associated with poor prognosis. A less invasive surgical approach for preserving anogenital and urinary functions may be acceptable as the first-line treatment for resectable EMPD.